“Características botánicas y agronomicas de híbridos de tabaco negro de capa bajo condiciones de riego en Juan Guerra San-Martín” - Huamán Carrero, Roiber (2015)
This research project called: "lnfluence of sources and rates of applied nitrogen and dry sheet of water to rice (Oryza satíva L.) under tillage system in Tarapoto - San Martin", lt was conducted at the Agricultura! Experimental Station "El Porvenir" - INIA - PNIA.Rice, within the period from March to July 2014, in order to determine the influence of incorporated nitrogen percentage of the nitrogen sources and types of aplication in the tillage system, on rice yields in variety INIA 509 - "La Esperanza". Where three factors are studied: Percentage of incorporated nitrogen (Factor N); Method of fertilization (Factor M); and nitrogen sources (Factor F), block design was completely randomized factorial arrangement of 2 x 2 x 3, with three replications. The results showed that fertilization in dry soil incorporated with water increase yields regardless of the nitrogen sources that are used, also showed that fertilization at a water depth is the traditional method that the rice farmer is practicing, making it lose significant amounts of nitrogen to the detriment of production, but you can increase the efficiency of nitrogen using inhibitory sources of urease and nitrogen sources composed with chemical mixtures of nitrogen with sulfur, these showed higher grain yields in shell, indicating that they have less losses when fertilized in water depths compared to urea. The results indicate that the use of high doses of water incorporated in the early stages (pre sowing) under nitrogen tropics have high risk of nitrogen losses caused by weather conditions such as precipitation and temperature, so that there is a limit tillering, panicle number and affecting crop yield of rice. The results indicate that soil fertilizations dry with twenty five percent of nitrogen incorporated with water, using any source of nitrogen increased the yield of paddy rice. The economic analysis determined that the treatments had relatively greater benefit cost was influenced by the cost of fertilizer.